2006
DOI: 10.3201/eid1207.040397
|View full text |Cite
|
Sign up to set email alerts
|

Rodent-associatedBartonellaFebrile Illness, Southwestern United States

Abstract: Patients showed seroconversion to rodent-associated Bartonella antigens, but not to Bartonella pathogenic for humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…The genus Bartonella is associated with aerobic, fastidious, gram-negative, slow-growing bacteria and consists of 20 species and three subspecies at the present time (19). These microorganisms infect the erythrocytes of their mammalian hosts, and some species cause a wide spectrum of illness, such as chronic bacteremia, fever, and endocarditis.…”
mentioning
confidence: 99%
“…The genus Bartonella is associated with aerobic, fastidious, gram-negative, slow-growing bacteria and consists of 20 species and three subspecies at the present time (19). These microorganisms infect the erythrocytes of their mammalian hosts, and some species cause a wide spectrum of illness, such as chronic bacteremia, fever, and endocarditis.…”
mentioning
confidence: 99%
“…positivity in mice and the role of ticks in the transmission of these agents (21). Iralu et al (2006) reported rodent-originated Bartonella infection in 9 of 76 patients (12%) with fever of unknown origin, diagnosed serologically with seroconversion and antibody presence in high titers (16). According to the present data, Bartonella infections should be among the differential diagnosis of cases with fever of unknown origin, which may be due to tick bites, and further studies should be performed accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…positivity in mice and the role of ticks as a transmitting agent (24). Iralu et al reported rodentborne Bartonella infection in 9 (12%) of 76 patients with fever of unknown origin, diagnosed serologically with seroconversion and high antibody titers (15). According to the available data in Turkey related to tick-borne infections with fever of unknown reason encourages us to study further.…”
Section: Discussionmentioning
confidence: 99%